Macro-and Micronutrients in Non-cow Milk and Products and Their Impact on Human Health - Fantuz, F.; Salimei, E.; Papademas, Photis (My University, 2016)
© 2016 Elsevier Inc. All rights reserved. Milk is known as the most complete single food available and is a fundamental ingredient of the human diet for both children and adults. Millions of people suffer for protein-energy malnutrition and micronutrient deficiencies, such as essential minerals and vitamins, also known as "hidden hunger." In this chapter the content of energy and macronutrients in milk from minor dairy species is compared to those in human and cow milk. The main lipids and nitrogen compounds are discussed in terms of possible beneficial or adverse effects on human health. The content of minerals and vitamins are also compared to the recommended nutrient intake for healthy children under 5. years of age and pregnant and lactating woman. In addition, the documented effects of consumption of milk or milk products from minor dairy species on human health are described, considering human and animal studies.
Keywords: Human health; Minor dairy species; Non-cow milk; Non-cow milk products; Nutrients